Influence of Hypertension and Lifestyle History on Stroke Occurrence Rates in Probolinggo District - Vivin Nur Hafifah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Stroke is a disease of the blood vessels of the brain that is characterized disruption of brain function due to damage or tissue death due to reduction or blockage of blood flow of oxygen to the brain. Blood flow to the brain is reduced due to narrowing, blockage or bleeding. Risk factors important to know in order to avoid and prevent stroke, these factors include hypertension and lifestyle. The purpose of this study untukd Analyzing Lifestyle History Of Hypertension And Stroke incidence rate in Probolinggo. The study design was analytic correlational with cross sectional approach. Collecting data using questionnaires, analysis of data with ordinal regression test at α = 0.05. The results showed that there is a history of hypertension influence on the incidence rate of stroke in Probolinggo amounted to 9.163 with sig. 0,047 (less than α (0:05)), there is the influence of a high-fat diet history against the incidence rate of stroke in Probolinggo amounted to 6.071 with sig. 0,014 (less than α (0:05)), there is less physical activity influence on the incidence rate of stroke in Probolinggo amounted to 3.788 with sig. 0,018 (less than α (0:05)), there is the influence of emotional stress on the incidence rate of stroke in Probolinggo amounted to 4,884 with sig. 0,034 (less than α (0:05)), there is the effect of smoking on the incidence rate of stroke in Probolinggo amounted to 3.317 with sig. 0,049 (less than α (0:05)).Based on these results, it is suggested that stroke patients to be able to control your blood pressure and can maintain a healthy lifestyle in order to avoid recurrent strokes